Estimation of cation-exchange capacity in routine soil testing - Niskanen, Raina; Jaakkola, Antti (Agricultural and Food Science, 1986)
The efficiency of the soil testing method used in Finland for predicting the effective cation-exchange capacity was studied in a material of 430 topsoil samples. The effective cation-exchange capacity was estimated 1) by summation of exchangeable Ca, Mg and acidity displaced by unbuffered 1 M KCI and 2) by summation of exchangeable Ca, Mg, K and Na displaced by neutral 1 M ammonium acetate and exchangeable acidity. In soil testing, Ca, Mg and K were extracted by acid ammonium acetate and soil pH measured in water-suspension. The estimates of the effective CEC were highly correlated and dependent on the clay and organic carbon content and pH(CaCl2) of the soil, the coefficient of multiple determination being over 80 %. Exchangeable Ca was the dominating cation. The proportion of Ca of the effective CEC was about 80 %. Acid ammonium acetate-extractable Ca together with pH(H2O) explained over 80 % of the variation in the effective CEC. For the whole material consisting of mineral soils with great variations in texture, organic carbon content and properties under evaluation, the regression equation predicting the effective CEC (KCI method) was CEC (mval/kg) = 309—56.8pH(H2O) + 0.085Ca(mg/l). Only 16 % of the estimates of the effective CEC calculated with this regression equation deviated more than 15 % from the measured values.